2021
DOI: 10.1088/1361-6501/abed85
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and uncertainty analysis of a combined tracking-based vision measurement system using Monte Carlo simulation

Abstract: A global stereovision system combined with a local vision sensor is an effective approach to large-scale object measurement. However, obtaining the error distribution of such an approach remains a key research challenge in vision metrological applications. This paper investigates the calibration and the reconstruction uncertainty estimation method of the combined vision system. The measurement principle and the calibration method of the transformation matrix between the tracking-based measurement coordinate sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…For a combined measurement system, data transformation will also bring more errors which can be reduced through calibration. Jiang et al [38] studied the error propagation and distribution of such a combined measurement system, putting forward that calibration of vision parameters and transformation matrices can reduce global error. Zhou et al [39] also suggested that combined calibration is required to determine and establish global and overall coordinate systems for data transformation.…”
Section: Related Workmentioning
confidence: 99%
“…For a combined measurement system, data transformation will also bring more errors which can be reduced through calibration. Jiang et al [38] studied the error propagation and distribution of such a combined measurement system, putting forward that calibration of vision parameters and transformation matrices can reduce global error. Zhou et al [39] also suggested that combined calibration is required to determine and establish global and overall coordinate systems for data transformation.…”
Section: Related Workmentioning
confidence: 99%
“…The key procedure for visual measurement is the motion extraction of image sequence. There are several methods for motion extraction [23][24][25]. In this paper, the phase-based motion extraction method suggested by Peng et al [25] was used to extract the displacement time histories of the measurement points in the video.…”
Section: Phase-based Visual Measurementmentioning
confidence: 99%
“…The linear profile sensor (LPS) has occupied a significant status in the field of 3D measurement for its high collection frequency, simplicity, and cost-effectiveness [15,[24][25][26][27][28][29][30][31]. Unlike RGB-D cameras and binocular vision instruments, the LPS employs a high-intensity, monochromatic light source, which renders it less susceptible to interference from ambient light, surface textures or colors of objects.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have proposed solutions to address this challenge. For instance, Jiang et al [29] and Liu et al [30] explored the measurement system incorporating LPS and rotating workbenches. Li et al [31] established a scanning measurement system by combining a linear laser with a galvanometer.…”
Section: Introductionmentioning
confidence: 99%